The perplexity of malignant ovarian mass in cystadenofibroma: a lesson learnt - Kathuria, Priyanka; Yadav, Garima; Singh, Pratibha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
The aim of this study is to report a rare case of ovarian cystadenofibroma with even scarcely observed mucinous type histopathological variant and to discuss the modalities which can contribute to prevent misdiagnosing it as a malignant tumor that may inappropriately lead to aggressive surgical interventions. A 40-year-old female presented with pain in lower abdomen and dysmenorrhea of 3 months duration and a large right adnexal mass which had all the features suggestive of malignancy in pre-operative investigations and even on gross overview and cut section. On the contrary histopathology reports confirmed its benign nature and reported it as mucinous cystadenofibroma. Role of Preoperative MRI and intraoperative frozen section cannot be overemphasized in distinguishing ovarian cystadenofibroma from malignant tumors, which can avoid an unnecessary extensive surgery.